Consensus guidelines for the management of adult low-grade gliomas for low and middle-income countries - Ahsan Ali Khan; Ayesha Akbar Waheed; Ali Azan Ahmed; Asim Hafiz; Adeeba Zaki; Ahmed Gilani; Faiza Urooj; Mohammad Hamza Bajwa; Pakistan Brain Tumour Consortium: (Authors list at the end of the supplement); Syed Ather Enam (Journal of the Pakistan Medical Association, 2024)
Low-grade gliomas (LGG) are brain tumors of glial cells origin. They are grade 1 and grade 2 tumors according to the WHO classification. Diagnosis of LGG is made through imaging, histopathological analysis, and use of molecular markers. Imaging alone does not establish the grade of the tumor and thus a histopathological examination of tissue is crucial in establishing the definite histopathological diagnosis. Clinical presentation varies according to the location and size of the tumor. Surgical resection is strongly recommended in LGG over observation to improve overall survival as surgery leads to greater benefit due to progression-free survival. Radiation has shown benefits in LGG patients in randomized controlled trials and chemotherapy with temozolomide has also shown good results. This paper covers the principles of low-grade gliomas management and summarizes the recommendations for the LMICs. Keywords: Temozolomide, survival, brain Neoplasms, glioma, neuroglia